Evaluating service performance at a community health center: Promethee and Lean Service methodologies - Febianti, Evi; Anggraeni, Shanti Kirana; Zhen, Alya Rahmayani; Wahyuni, Nuraida; Ekawati, Ratna (Journal Industrial Servicess, 2023)
Puskesmas XYZ, situated in Cilegon City, serves one or multiple sub-districts as a primary healthcare facility, boasting a commendable performance rating of 3.66. To elevate service quality, the Mayor of Cilegon has suggested transitioning to the Regional Public Service Agency system, granting the health center operational autonomy apart from local government dependencies. Despite its laudable performance, Puskesmas XYZ requires enhancements to adopt the BLUD system, as indicated in Cilegon's 2020 Public Service Assessment Report. The report highlights six areas necessitating improvement: service policies, professional human resources, information systems, facilities, and infrastructure, as well as consultation and complaint mechanisms. This study aims to assess and prioritize improvement strategies using the Servperf model and PROMETHEE method. PROMETHEE calculations identified 10 alternatives with negative net flow: E4, RS2, TA3, E3, E5, AS2, RS3, AS1, RS4, and E1. Moreover, the process definition mapping identified 5 alternatives with activity flows across administration, general polyclinic, and pharmacy sections. This breakdown includes 11 activities as VA, 7 as NVA, and 2 as NNVA. Additionally, a root cause analysis (RCA) employing the 5 Whys method was conducted to identify issues and propose viable enhancements for Puskesmas XYZ. These measures aim to empower the health center, fortify its services, rectify weaknesses, and ultimately bolster healthcare provisions for the community.